PATHOGENIC ORGANISMS IN THE ENVIRONMENT OF A TEACHING HOSPITAL - Khan, Mir Hassan; Khan, Jahangir A.; Bukhari, Attaullah Shah; Khan, Jaffar (Journal of Ayub Medical College Abbottabad, 1992)
ABSTRACT: A survey of bacterial organisms was carried out at District Headquarter leaching Hospital, Abbottabad. It was observed that pathogenic organisms in the hospital environment were quite high as compared to clean area outside the hospital. These micro-organisms were isolated from hands, clothes, nose, car and throat of various staff members and at different places and accessories of the hospital. The predominant organisms found were Staphylococcus aureus, Staphylococcus albus and Escherichia coli.